Combined Use of Bicyclol and Berberine Alleviates Mouse Nonalcoholic Fatty Liver Disease - Li, Hu; Liu, Nan-Nan; Li, Jian-Rui; Dong, Biao; Wang, Mei-Xi; Tan, Jia-Li; Wang, Xue-Kai; Jiang, Jing; Lei, Lei; Li, Hong-Ying; Sun, Han; Jiang, Jian-Dong; et al. (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD), ranging from simple steatosis to nonalcoholic steatohepatitis (NASH), is a liver disease worldwide without approved therapeutic drugs. Anti-inflammatory and hepatoprotective drug bicyclol and multi-pharmacological active drug berberine, respectively, have shown beneficial effects on NAFLD in murine nutritional models and patients, though the therapeutic mechanisms remain to be illustrated. Here, we investigated the combined effects of bicyclol and berberine on mouse steatosis induced by western diet (WD), and NASH induced by WD/CCl4. The combined use of them was rather safe, and better reduced the levels of transaminase in serum and triglycerides and cholesterol in the liver than their respective monotherapy, accompanying with more significantly attenuating hepatic inflammation, steatosis, and ballooning in mice with steatosis and NASH. The combined therapy also significantly inhibited the fibrogenesis, characterized by the decreased hepatic collagen deposition and fibrotic surface. Mechanismly, bicyclol enhanced lipolysis and β-oxidation through restoring p62-Nrf2-CES2 signaling axis and p62-Nrf2-PPARα signaling axis, respectively, while berberine suppressed de novo lipogenesis through down-regulating the expression of acetyl-CoA carboxylase and fatty acid synthetase, along with enrichment of lipid metabolism-related Bacteroidaceae (family) and Bacteroides (genus). Of note, combined use of bicyclol and berberine did not influence each other but enhance the overall therapeutic role in the amelioration of NAFLD. Conclusion: Combined use of bicyclol and berberine might be a new available strategy to treat NAFLD.